Are We Throwing out the Books with the Bathwater?: Dilemmas over New Directions in Library Design. - Smith, Charlie (International Journal of the Book, 2017)
The growing popularity of digital media has led to a fundamental re-evaluation of the role of libraries as they strive to maintain their relevance to their patrons' changing needs. This is having a significant impact on their design and space use requirements, including a reduction in the areas dedicated to book stacks. However, recent research suggests that the trend toward digital may be changing with a resurgence of physical media. Is there risk of losing the essential qualities that make libraries such distinct and appealing places as stacks are replaced by more informal spaces and increasingly diverse activities? This article discusses trends in library design, investigates the long-term effects of adopting new activities, and considers the extent to which these new activities should replace books. Referring to recent research on reading habits and to examples of contemporary library architecture, this article cautions against the wholesale relegation or removal of physical books for a number of reasons--not least because buildings evolve much more slowly than digital technologies, and once adaptations are made they are likely to be long lived.